The slave dancer - Fox, Paula (New York Dell, 1973)
Kidnapped by the crew of an Africa-bound ship, a thirteen-year-old boy discovers to his horror that he is on a slaver and his job is to play music for the exercise periods of the human cargo
English stories
2
Keywords: English stories